Phenological shifts in conifer species stressed by spruce budworm defoliation. (28th December 2018) - Deslauriers, Annie; Fournier, Marie-Pier; Cartenì, Fabrizio; Mackay, John
Abstract: Synchrony between host budburst and insect emergence greatly influences the time window for insect development and survival. A few alterations of bud phenology have been reported under defoliation without clear consensus regarding the direction of effects, i.e., advance or delay. Here, we compared budburst phenology between conifers in defoliation and control treatments, and measured carbon allocation as a potential mechanistic explanation of changes in phenology. In a 2-year greenhouse experiment, saplings of balsam fir, black spruce and white spruce of two different provenances (north and south) were subjected to either control (no larvae) or natural defoliation treatment (larvae added) by spruce budworm. Bud and instar phenology, primary and secondary growth, defoliation and non-structural carbohydrates were studied during the growing season. No differences were observed in bud phenology during the first year of defoliation. After 1 year of defoliation, bud phenology advanced by 6–7 days in black spruce and balsam fir and by 3.5 days in white spruce compared with the control. Because of this earlier bud break, apical and shoot growth exceeded 50% of its final length before mature instar defoliation occurred, which decreased the overall level of damage. A sugar-mediated response, via earlier starch breakdown, and higher sugar availability to buds explains the advanced budburst in defoliated saplings. The advanced phenological response to defoliation was consistent across the conifer species and provenances except for one species × provenance combination. Allocation of carbon to buds and shoots growth at the expense of wood growth in the stem and reserve accumulation represents a shift in the physiological resources priorities to ensure tree survival. This advancement in bud phenology could be considered as a physiological response to defoliation based on carbohydrate needs for primary growth, rather than a resistance trait to spruce budworm.